Thromboelastography in obese horses with insulin dysregulation compared to healthy controls. - Lovett AL; Gilliam LL; Sykes BW; McFarlane D (John Wiley and Sons, Inc., 2022)
BACKGROUND: Both obesity and metabolic syndrome are associated with hypercoagulability in people, increasing the risk of cardiovascular disease and thromboembolic events. Whether hypercoagulability exists in obese, insulin-dysregulated horses is unknown. HYPOTHESIS/OBJECTIVES: To determine if coagulation profiles differ between healthy horses and those with obesity and insulin dysregulation. ANIMALS: Fifteen healthy horses (CON) and 15 obese, insulin-dysregulated horses (OBID). Individuals were university or client owned. METHODS: Case-control study. Obesity was defined as a body condition score (BCS) ≥7.5/9 (modified Henneke scale). Insulin dysregulation status was assessed by an oral sugar test (OST). Kaolin-thromboelastography and traditional coagulation variables were compared between groups. The direction and strength of the association between coagulation variables and BCS and OST results were determined using Spearman's correlation. RESULTS: Thromboelastography variables MA (OBID: 69.5 ± 4.5 mm; CON: 64.8 ± 4.3 mm; P = .007) and G-value (OBID: 11749 ± 2536 dyn/m2 ; CON: 9319 ± 1650 dyn/m2 ; P = .004) were higher in OBID compared to CON. Positive correlations between MA and BCS (R = 0.45, P = .01) and serum insulin (T0 : R = 0.45, P = .01; T60 : R = 0.39, P = .03), and G-value and BCS (R = 0.46, P = .01), and serum insulin (T0 : R = 0.48, P = .007; T60 : R = 0.43, P = .02; T90 : R = 0.38, P = .04) were present. CONCLUSIONS AND CLINICAL IMPORTANCE: Obese, insulin-dysregulated horses are hypercoagulable compared to healthy controls.
Keywords: equine metabolic syndrome; hemostasis; hypercoagulability; obesity; oral sugar test; viscoelastic testing; Animals; Case-Control Studies; Horse Diseases; Horses; Humans; Insulin; Obesity; Thrombelastography; Thrombophilia